Nematic ordering of semiflexible polymers confined on a toroidal surface. Issue 24 (1st June 2016) - Ye, Shiwei; Zhang, Pingwen; Chen, Jeff Z. Y.
Abstract : The influence of the surface curvature of a torus on the isotropic-like and nematic textures of a surface-confined liquid-crystal polymer fluid. Abstract : We study the isotropic-like and nematic states of wormlike liquid-crystal polymers embedded on the surface of a torus. The role played by surface curvature, which couples to the molecular rigidity, is reported as the main reason that causes the weak nematic ordering in an otherwise ordinary isotropic phase. The same coupling has a profound effect on the nematic states as well, which are stabilized by the Onsager excluded-volume interaction; the latter has been frequently used to study lyotropic liquid crystal polymers and is used here as an example of the physical mechanisms that drive the system to make orientational ordering. We identify important parameters in the system which are used as axes of the four-dimensional phase diagram. The numerical study demonstrates a strong correlation between the liquid-crystal defect-free and defect structures and the geometry of the liquid-crystal embedded surface.